Integrasi Ekowisata dan Community-Based Tourism (CBT) dalam Pengelolaan Berkelanjutan Clungup Mangrove Conservation (CMC) Tiga Warna - Zaki Alif Ramadhani; Annisa Lazuardina; Nadya Mutiara Yasin; Rizky Ja'far Sodig (Yayasan Literasi Sains Indonesia, 2026)
Clungup Mangrove Conservation (CMC) Tiga Warna is a coastal ecotourism destination managed through a community-based approach that successfully integrates environmental conservation with local empowerment. This study aims to analyze the application of ecotourism and community-based tourism (CBT) principles in the area and assess their contribution to ecological and economic sustainability. The findings indicate that the restoration of mangroves, coral reefs, and coastal ecosystems is directly supported by strict visitor management, carrying-capacity regulation, and the reinvestment of tourism revenue into conservation programs. Field evidence reveals that ecological improvements have led to increased fish catches, improved freshwater availability, enhanced soil fertility, and reduced environmental risks for surrounding communities. Economically, CMC has experienced increasing revenue trends from 2022 to 2024, with profits fully reinvested into conservation and community operations. The integration of ecotourism and CBT principles is reflected in strong community participation in decision-making, financial transparency, equitable benefit distribution, and the development of local capacities in conservation and tourism services. Overall, CMC Tiga Warna demonstrates that a community-based management model can effectively support ecotourism objectives while enhancing the well-being and resilience of coastal communities.